2010
DOI: 10.1002/cncr.25480
|View full text |Cite
|
Sign up to set email alerts
|

Does the progression‐free interval after primary chemotherapy predict survival after salvage chemotherapy in advanced and recurrent endometrial cancer?

Abstract: BACKGROUND: This study evaluated whether progression-free interval (PFI) following primary chemotherapy (PCT) was predictive of overall survival (OS) after second-line chemotherapy in advanced/recurrent endometrial cancer (EC). METHODS: This is a pooled analysis of patients who recurred after PCT and were treated with second-line chemotherapy on Gynecologic Oncology Group trials. PFI-1 measured from initiation of PCT to recurrence or treatment-free interval (TFI) measured from completion of PCT to initiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
(37 reference statements)
2
13
0
1
Order By: Relevance
“…Median survival after endometrial cancer recurrence in this study was 21 months, consistent with previous descriptions of the dismal prognosis of recurrent endometrial cancer 5 7–10 12 23. Yet, post-relapse survival was significantly influenced by the pattern of recurrence, with the best prognoses found in patients with lymphatic recurrences and the worst in those with mesothelial or mixed recurrence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Median survival after endometrial cancer recurrence in this study was 21 months, consistent with previous descriptions of the dismal prognosis of recurrent endometrial cancer 5 7–10 12 23. Yet, post-relapse survival was significantly influenced by the pattern of recurrence, with the best prognoses found in patients with lymphatic recurrences and the worst in those with mesothelial or mixed recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…This finding indicates that single pathway recurrent endometrial cancer may be less deregulated and more biologically similar to the primary tumor than multiple pathway recurrent endometrial cancer. In this context it is important to highlight the controversial prognostic role of time to recurrence: few studies have suggested that a time to recurrence longer than 6–12 months is associated with better post-relapse survival 7 8. In our multivariate analysis, time to recurrence was not a significant predictor of post-relapse survival in the overall population or in sub-group analyses, suggesting that, unlike ovarian cancer, a short time to recurrence in endometrial cancer does not necessarily indicate treatment resistance, but may be related to the persistence of microscopic disease after primary treatment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although various regimens have been evaluated in this setting,189192 no randomised trials have been published. Therefore, no specific regimen can be recommended as a standard of care for second line chemotherapy.…”
Section: Advanced and Recurrent Endometrial Cancermentioning
confidence: 99%
“…8 That study also suggested that TFI is an important indicator when single agents are used as second-line chemotherapy for endometrial cancer. These findings raise the possibility that TFI or PFI could be used in selecting the second-line chemotherapy regimen in cervical cancer.…”
mentioning
confidence: 92%